DOMPET DIGITAL APLIKASI DANA MEMBERIKAN KEMUDAHAN DALAM BERTRANSAKSI SECARA ONLINE - Aizza Nuramalia (2021)
The Financial Industry is growing with the presence of Financial Technology (Fintech) which has emerged along with the increasing needs and changes in the lifestyle of an all-digital society. The presence of Fintech that combines technological sophistication with financial services can be the right solution for the community. The development of fintech can have a positive impact on the economy. This has triggered the emergence of various fintech companies, one of which is DANA. DANA as a digital wallet application is here to answer the needs of the community by offering convenience in online transactions. This is shown through its work since it was inaugurated in 2018, DANA is in demand by the public with an increasing number of users. The purpose of this paper is to find out the ease of DANA in transacting through the mechanism of its use and the benefits felt by DANA users. The results achieved indicate that DANA plays a role in providing benefits in the form of quality and convenience that are packaged in the advanced features of a fintech application. DANA provides easy access to various kinds of transactions with just the touch of a finger. The clear and user-friendly appearance and system of DANA makes it easier to use.